Problematika PKN di Sekolah yang Berbasis Agama di Perkotaan - Muhammad Sa’dii Fathir; Muhammad Turhan Yani; Harmanto; Agus Suprijono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Citizenship training has the significance of being a vehicle for character schooling which is worked to encourage and foster shrewd and productive members of society in formal, casual and non-formal training channels which have become piece of the objectives of public instruction in Indonesia. From the consequences of the writing concentrate on that I found, it was uncovered that Civics learning or subjects assume a vital part in learning. This is because of the nature and objectives of Civics subjects which contain values that can be implemented into life so that we can become good citizens or good citizenship. The article writing method is a descriptive qualitative method using literature studies and library research. Then the results of this article are about Civics Problems in Religious Based Schools in Urban Areas. Civics Problems in Religious Based Schools in Urban Areas at this time are basically what Citizenship Education is experiencing is still the same as in previous years, namely that it still prioritizes cognitive aspects, so the aim is to create students who are critical and responsible. still not realized. In fact, most students think that Citizenship Education subjects are formal learning and are only a requirement.